Pedaling stroke length effects on the muscle mechanical and electrical activity during recumbent cycling - Fukuhara, S.; Oka, H. (Gazzetta Medica Italiana - Archivio per le Scienze Mediche, 2021)
BACKGROUND: A thorough assessment of the muscle function during exercise requires inspections of both electrical and mechanical activity of the muscle. While several evaluations of the electrical activity of the muscles during pedaling are available through the electromyography (EMG) tests, the evidence of mechanical activity via mechanomyography (MMG) tests are lacking significantly. This study aimed to investigate the effect of the pedaling stroke length on MMG, EMG, and their correlation by using our advanced MMG/EMG hybrid transducer system. METHODS: The target exercise was to pedal a recumbent bicycle; the displacement-MMG (dMMG) and EMG of the vastus medialis were measured. The knee joint angle was adjusted to 90°, 100°, and 110° with respect to the pedal`s top dead center, consequently changing the pedaling stroke length. RESULTS: The results showed that: 1) both dMMG and EMG values increase with a decreasing pedaling length; and 2) the correlation between the normalized dMMG and EMG showed a distinct proportionality and a larger slope of the regression line for a shorter pedaling length. CONCLUSIONS: The results of this study revealed that the differences in the range of motion during pedaling affect the mechanical activity and the performance of the knee extensor muscle. Further systematic evaluation based on dMMG and EMG combined can contribute to the clinical evidence.